2017
DOI: 10.1108/jd-09-2016-0111
|View full text |Cite
|
Sign up to set email alerts
|

Choosing a book by its cover: analysis of a reader’s choice

Abstract: Purpose The massive growth in the number of book titles has made publishers think about how to attract a customer’s attention to particular books. This is the reason why the book cover plays an important role as a tool of communication with the reader. The research question of this exploratory study is whether the preference given by readers to book cover colors is different across genders and age groups when they choose the book in an online bookstore by its cover. The paper aims to discuss these issues. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
0
20
2
1
Order By: Relevance
“…This cover takes into consideration the choice of reading and content by readers (Gudinavičius & Šuminas, 2018).…”
Section: Expertmentioning
confidence: 99%
“…This cover takes into consideration the choice of reading and content by readers (Gudinavičius & Šuminas, 2018).…”
Section: Expertmentioning
confidence: 99%
“…The summary is used to review the main ideas of the material that has been presented so that there are opportunities for students to remember the material that has been presented. So the summary is a component of a strategy that covers all the contents of an important field of study, such as understanding a brief understanding of the concepts, procedures, or principles learned [16]. The use of summaries is something that can be given in the learning process to recall important information that has been learned previously.…”
Section: A Ideal Book Characteristicsmentioning
confidence: 99%
“…The results showed that most time was spent assessing a somewhat interesting novel compared to a non-interesting or very interesting one. Gudinavičius and Šuminas (2018) did experiment to explore the relationship between the users’ preference of book cover colors and their choice of book in an online bookstore by its cover. The study found a significant positive correlation between the women’s preferences in selecting covers and the time women spent looking at them; however, there was no such correlation in the case of the men’s data.…”
Section: Literature Reviewmentioning
confidence: 99%